Investigation of Multi-ionization Processes of Kr and Xe Using Short-pulse X-rays and Time-of-flight Apparatus. (3rd March 2023) - Gejo, Tatsuo; Tanaka, Yuka; Sakano, Takuya; Takeuchi, Satoshi; Takahashi, Osamu; Osawa, Hitoshi; Sugimoto, Kunihisa; Tamasaku, Kenji; Oura, Masaki
Abstract: The multi-ionization processes of Kr and Xe in the K- edge photon energy region were investigated using short-pulse x-rays and time-of-flight apparatus. The generation of Kr 13+ ions in this photon energy region was observed for the first time. The distribution characteristics observed in the experiment, such as the production of Kr 13+ ions, high production ratios of Kr 4+, Kr 5+, and Kr 6+ ions, and the existence of a small peak for Kr 8+, were quantitatively reproduced by the Monte Carlo simulation for the charge distribution of Kr ions following 1 s of inner shell ionization. The highly charged ions were suppressed in the experiments compared with those in the simulation, probably owing to the inhibition of certain Coster-Kronig processes in the highly charged ions, which were not considered for analysis. The charge distribution of Xe ions following 1 s of inner shell ionization was also investigated. A similar charge distribution was observed when the photon energy was located between the K and L edges. This is because the Xe 1 s hole state mainly undergoes ultrafast relaxation to the 2 p hole state owing to the strong dipole transition moment between the 1 s and 2 p states.